Relationship Of Calcium Levels To Hypertension In Pregnancy - Nur Elly; Erli Zainal; Iin Nilawati (Alma Ata University Press, 2020)
Pregnancy-induced hypertension often progresses to pre-eclampsia as one of the biggest contributors to maternal mortality. Mineral and nutritional factors have an important role in the etiology of pregnancy-induced hypertension, especially pre-eclampsia. A mineral factor associated with hypertension is calcium. This study attempts to analyze the relationship between calcium levels and the occurance of pregnancy-induced hypertension. A cross-sectional study design was used to measure or observe independent variables (calcium levels) and dependent variables (hypertension in pregnancy). The number of samples was 43 second-trimester pregnant women taken by consecutive sampling technique. This study used primary data by examining blood pressure and calcium levels contained in the blood serum of pregnant women. Univariate analysis results showed that 30% of pregnant women experienced pregnancy-induced hypertention, and 44% of pregnant women had insufficient calcium levels. The results of the bivariate analysis proved that there was a significant correlation between maternal blood calcium levels and the occurence of hypertension in second-trimester of pregnant women (p value 0,000).